MOTIVASI BERWIRAUSAHA PADA PENYANDANG DISABILITAS FISIK - Winasti, Milu (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThis study aims to determine motivation of entrepreneurship in peoplewith physical disabilities, factors that become obstacles in entrepreneurship,and how to overcome the obstacles that occurred. Subjects in this research istwo persons with physical disabilities acquired.The research method used was a qualitative phenomenological approachand using content analysis. Data collection techniques with semi-structuredinterviews, non-participant observation and field notes. Thisresearch also complete the the data by interviewing the significsnt personasa triangulator.The results showed that entrepreneurial motivation in people with physicaldisabilities is to to support his family, build a relationship withpeople, helpingpeople with physical disabilities to be more prosperous, theexistence ofself esteem, the desire to align with normal people. Factorsthat become obstacles in the work comes from external factors which factors ofproduction and labor issues, marketing issues, financing, design, qualityofproducts and partners. Both subjects to overcome obstacles using theproblemfocused coping strategies.The conclusion of this research that entrepreneurial motivation inpeoplewith physical disabilities is driven by the needs of existence, relationshipsand growth. Obstacles were found is a factor of production and employment,marketing, financing, design, quality products, and partners. How toovercome the obstacles subjects using problem focused coping strategies suchas planfull problem solving, direct action, asistence seeking and informationseeking.Keywords: motivation, physical disabilities, obstacles, problem focused coping